Translation Specifics and Equivalence in Professional English Terms - Ayaqulov Nurbek Abdug‘appor o‘g‘li; Xidirov Olmosbek Abdurazak o‘g‘li (Open Academia, 2024)
This study aims to examine the nuances of translating English terms in professional texts. It focuses on distinguishing how single-component and multi-component terms function differently. Findings indicate that an abundance of multi-component terms reflects an underdeveloped terminology system, resulting in relative translation equivalence, contrasting with the clearer translation equivalence found in single-component terms. Transformational translation methods are shown to broaden the semantic scope of terms in the target language
Keywords: terminological system; one-component term; professionally oriented text